PENERAPAN PENGENDALIAN INTERNAL DALAM SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER - Putu Mega Selvya Aviana (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Accounting information systems related to the company's business activities such as classifying, recording and communicating information as a result of the end to reach a good decision for the internal parties and external parties, along with the development of technology, the accounting information system switched from manual to computerized. This paper aims to unravel the implementation of internal controls in accounting information systems and the role of internal control systems to evaluate and improve the system of accounting information. Information systems, computerbased accounting, which is where all the business processes using computerized processes. The use of accounting information systems computer-based in its implementation does not escape from the risks that occur, either intentionally risk or unintentionally risk. Companies that use information systems computer-based accounting requires that internal controls are integrated to produce the maximum, thus helping companies to minimize risks that may occur in connection with the use of computer-based accounting information systems to business processes.